Torsional Stiffness Improvement of Truck Chassis Using Finite Elemen Method - Kurdi, Ojo; Rahman, Roslan Abdul; Samin, Pakharudin Mohd; Yob, Mohd Shukri; Nadarajan, Nantha Kumar; Yulianti, Ian (ROTASI, 2017)
This thesis deals with a study on the torsional stiffness of existing truck chassis and some others improved models by using finite element method. The objective of this study is to improve the torsional stiffness by design and to provide simulation of the deflection on the chassis. The problem on the chassis is the deflection on the chassis whereas  higher  displacement  will  affect  the  torsional  stiffness  of  the  truck. ABAQUS was used as it is a powerful engineering simulation tool based on the finite element method. The magnitude of torsional stiffness for existing and modified models were calculated based on data of deflection of each models which were obtained from the finite element simulation. The multi holes model was choosen as the best proposed model due to the highest of torsional stffness as comparison result among existing and modified models.